KEBIJAKAN RESOLUSI (Pembangunan Bendungan Boiya Sidrap-Enrekang) - Barisan, Barisan; Haeruddin, Haeruddin (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2018)
This  research aim to know and  analysis steps resolution by complic the dam growing plan at Boya Enrekang Regency. This complict begin from there was policy governrment who plan act build a dam. This policy get  opposed from the people distric Maiwa speciaally from the villages will destroyed after build this dam.As  the result, this researh pind out strategic manage complict who use this era is silent problem seems the builds will not realisation. So step complict resolution who effering is government must be used compromis to the people. So ready  to get policy, but government nust be change their fields whose destroyed. With new fields, so government give an accomodation as asubsidi for the peopel who was moved.